2021
DOI: 10.12775/jehs.2021.11.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Stretching and injuries in men undertaking running training

Abstract: A permission to conduct this study was obtained from the Bioethics Committee of the Ludwik Rydygier Collegium Medicum of Nicolaus Copernicus University in Toruń (no. KB 787/2014). All men were informed about the purpose of the study, type and duration of the effort, and the possibility to withdraw from the study without giving any reason. Each potential participant granted a voluntary consent for participation in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…To achieve the sports training injury risk assessment model, the big data fusion scheduling method is used for big data information sampling of sports training injury risk assessment, combined with the statistical information mining method for sports training injury risk assessment, dividing the level of sports training injury risk assessment X (0) , into N levels, as X (1) , X (2) , ..., X (N) , that is, X (0) � ∪ N i�1 X (i) , with the fuzzy feature distributed mining method for statistical analysis and optimal assessment of sports training injury risk, establishing a big data analysis model for sports training injury risk assessment and adaptive learning for sports training injury risk assessment and obtaining a statistical function for sports training injury risk assessment as [11] min…”
Section: Mobile Information Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the sports training injury risk assessment model, the big data fusion scheduling method is used for big data information sampling of sports training injury risk assessment, combined with the statistical information mining method for sports training injury risk assessment, dividing the level of sports training injury risk assessment X (0) , into N levels, as X (1) , X (2) , ..., X (N) , that is, X (0) � ∪ N i�1 X (i) , with the fuzzy feature distributed mining method for statistical analysis and optimal assessment of sports training injury risk, establishing a big data analysis model for sports training injury risk assessment and adaptive learning for sports training injury risk assessment and obtaining a statistical function for sports training injury risk assessment as [11] min…”
Section: Mobile Information Systemsmentioning
confidence: 99%
“…is risk factor refers to the existence of an old sports injury in the athlete's body, but the athlete does not pay enough attention or insists on participating in training with the injury due to psychological factors that lead to aggravation or new sports injuries. Taking China's outstanding Latin dance players as an example, [10] investigated 48 study subjects and found that 60.45% of the players continued training after the occurrence of sports injuries with only simple treatment and 23.1596 players still trained normally [11]. Exercise fatigue is the inability of the physiological processes of the body to sustain [12].…”
Section: Introductionmentioning
confidence: 99%